Meningkatkan Kemampuan Penalaran Matematis Siswa Melalaui Pembelajaran Berbasis Masalah Menggunakan Teachmint - Arisan Candra Nainggolan; Kms. Muhammad Amin Fauz; Pardomuan Sitompul (Journal on Education, 2023)
In an era of progress intelligence artificial moment this, there Lots study about supported learning technology learning. However , still little is known about learning Assisted Problem Based Learning (PBL) . Teachmint in support ability reasoning math. Study This aim For test And analyze difference enhancement ability reasoning the math that follows learning Assisted Problem Based Learning (PBL) . Teachmint And learning expository. Study This use method quantitative with a nonequivalent quasi-experimental pretest posttest control-group design. Sample consists of 70 second semester PGSD students university Catholic Saint Thomas Medan. Before And after learning , research data collected with use test reasoning composed mathematics of 5 questions essay. Analysis sample -t test in pairs And independent -t test used For answer hypothesis research. Results study conclude that studying students Assisted Problem Based Learning (PBL) with Teachmint obtain enhancement ability reasoning more math tall compared to studying with expository, with criteria enhancement ability on second class is at on category medium .